Analisis Prestasi Belajar Mahasiswa Ditinjau dari Jurusan SMA, Jenis Kelamin, Jalur Masuk, dan Asal Daerah serta Implikasinya terhadap Kebijakan Penerimaan Mahasiswa Baru - Himmah, Fara (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2021)
Academic performance of students, is an important thing in higher education institutions. The purpose of this study is to obtain empirical information that can be used to analyze differences in learning achievement between students from the path of entering high school majors, gender and regional origin and determine future student recruitment policies. Quantitative is methods of this research .using hypothesis a sample T-Test for comparing two different samples in pairs. The results in this study are There are significant and simultaneous influences of high school entrance and majors on student performance, There is a significant influence on high school majors on student achievement, There is a significant of gender on student IPK and there is no significant result from the region on student achievement.